A research on the innovative performance of clustering enterprises in industrial parks: Evidence from Shenzhen, China - BAI, Jiangong (Institutional Knowledge at Singapore Management University, 2022)
How about the innovation performance of enterprises clustered in the industrial parks? This is the core question of this study. Based on the thinking and evolution of the question, this study will focus on the impact of industrial agglomeration on enterprise innovation performance with enterprise relations and informal institution as intermediate variables. In this study, Shenzhen, as a city of innovation, is selected as the research area where sample parks and enterprises can be investigated to obtain data. This study constructs and measures the strength of informal institution and enterprise innovation performance through grounded theory and fuzzy matter-element method, evaluates the enterprise relationship in the parks through social network analysis(SNA), and then takes cluster enterprises, the operation of industrial park, enterprise relations in the parks and enterprise innovation performance as four variable sets, build models, and use the method of regression analysis to judge the impact of various factors on enterprise innovation performance in the industrial parks. This study found that the industrial agglomeration has no direct and significant positive impact on the network of clustering enterprises, but significant positive impact on enterprise innovation performance. Network and informal institution also have significant positive impact on enterprise innovation performance, and informal institution has an intermediary effect between industrial cluster and enterprise innovation. Especially in Shenzhen, the informal institutional relationship consisted of blood, geography, industry and learning plays an important role. For industrial parks with a certain scale, due to industrial upgrading and renewal, they pay more attention to the exploration of the potential of innovative enterprises, and even give considerable preferential policies to actively guide them to settle in and promote their innovation performance.